(untitled) (ARTEKS : Jurnal Teknik Arsitektur, 2020)
Globalization is being experienced throughout the world with its impact also observed in architecture, even in traditional villages of Indonesia. Some of them have, however, been able to maintain their identity such as the mass-space pattern of the customary village of Bali Aga Mountains in Bali which is discovered not to have changed. This research was, therefore, conducted to determine the relationship between the activities of the traditional society and their mass-space patterns using the customary village of Bali Aga Tenganan Pegringsingan as the case study. This involved the selection of respondents purposively and collection of data using cross sections by identifying unchanged buildings, taking photos, videos, drones, and through direct interviews in the field. The data obtained were analyzed qualitatively based on structuring theory or ordering principles and the results confirmed the mass-space pattern in Tenganan Pegringsingan village was built due to the close relations with the traditional activities of the society. The findings can be used in developing architecture by local governments as policymakers as well as academic architects and practitioners, and the wider society. © 2020 Lydia Dewi Setiawan, Purnama Salura, Bachtiar Fauzy